On Sensitivity and expansivity of Linear Random DYnamical systems - rafal HAMZAH; Ihsan Jabbar Kadhim (Al-Qadisiyah Journal of Pure Science, 2021)
in this study we introduce and study  of on Sensitivity  and expansivity  of Linear  Random DYnamical systemsWe obtain various  important  properties  and  theorems about Sensitivity Random DYnamical  systems and Expansivity  Random DYnamical systems